Incentives, Exports and International Competitiveness in Sub-Saharan Africa : Lessons from the Apparel Industry - Conway, Patrick (Washington, DC, 2013)
This country-level analysis of international trading patterns examines all sub-Saharan (SSA) countries for which trade data exist. Firm-level analysis is restricted to five countries: Kenya, Mauritius, Madagascar, Swaziland, and Lesotho, for which enterprise surveys are available from the period just before or after the elimination of the final quotas in 2005, under the Agreement for Textiles and Clothing (ATC). Comparators were selected from Asia (Bangladesh, Indonesia, Vietnam), and North Africa (Morocco, Egypt), as benchmarks for the SSA countries, and also to examine their performance relative to normal world trading patterns and volumes. The findings, along with corresponding policy recommendations, are summarized, and key issues are addressed, including which countries adjusted to this with lowest cost; what lessons can the SSA countries draw from this episode in their negotiation and exploitation of trade preferences offered by the US, EU and other potential markets; and how does an SSA country create or attract an export-ready apparel firm. Does the poor performance of sub-Saharan African (SSA) exporters in the period since the removal of quotas in 2005, imply that SSA countries do not have a comparative advantage in apparel, and thus should focus development efforts on other sectors? This report focussed on the evolution of the apparel trade with the removal of ATC quotas. It is important, though, to recognize that African apparel exporters have now been through two negative shocks, the end of trade diversion with the ending of the ATC quota system, and the trade elimination through demand reduction in the US and EU in the aftermath of the financial crisis of 2008.